2006
DOI: 10.1038/sj.ki.5001788
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplant hypophosphatemia: Tertiary ‘Hyper-Phosphatoninism’?

Abstract: Hypophosphatemia is a common complication of kidney transplantation. Tertiary hyperparathyroidism has long been thought to be the etiology, but hypophosphatemia can occur despite low parathyroid hormone (PTH) levels and can persist after high PTH levels normalize. Furthermore, even in the setting of normal allograft function, hypophosphatemia, and hyperparathyroidism, calcitriol levels remain inappropriately low following transplantation, suggesting that mechanisms other than PTH contribute. Fibroblast growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
136
3
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(160 citation statements)
references
References 47 publications
16
136
3
5
Order By: Relevance
“…This observation strengthens the notion of inappropriate hyperphosphatoninism in the early posttransplant period as put forward in previous reports (3,4). After M3, however, FGF-23 levels showed a further decline to reach concentrations at M12 that were similar to those of CKD counterparts.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This observation strengthens the notion of inappropriate hyperphosphatoninism in the early posttransplant period as put forward in previous reports (3,4). After M3, however, FGF-23 levels showed a further decline to reach concentrations at M12 that were similar to those of CKD counterparts.…”
Section: Discussionsupporting
confidence: 72%
“…Persistence of inappropriately high serum levels of fibroblast growth factor-23 (FGF-23), a recently discovered phosphaturic hormone, plays an important role in the pathogenesis of this complication (3,4).…”
mentioning
confidence: 99%
“…It is recognized that both hypophosphatemia and renal phosphate wasting may have a detrimental impact on bone mineralization (3,4). We and others recently reported that renal phosphate wasting in the post-transplant period is caused, at least partly, by the persistence of inappropriately high levels of fibroblast growth factor 23 (FGF-23) (5,6). This condition is often referred to as "tertiary hyperphosphatoninism."…”
mentioning
confidence: 99%
“…FGF23 levels are increased in chronic kidney disease (31, 80,85,86) and may be involved in the development of secondary hyperparathyroidism (87). FGF23 may also be important in the hypophosphatemia observed early after kidney transplantation and in nephrolithiasis associated with a renal leak of phosphate (88,89).…”
Section: Fgf23 As a Phosphaturic Hormonementioning
confidence: 99%